Thermodynamic study of Ti-V and Al-V systems using FactSage - Kostov A.; Živković D.; Friedrich B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Thermodynamic study of Ti-V and Al-V binary systems is presented in this paper. Investigations included thermodynamic determination of activities, coefficient of activities, partial and integral values Gibbs energies of mixing and excess energies at four different temperatures: 2000K, 2073K, 2200K and 2273K, as well as calculated phase diagrams for the investigated systems. The FactSage program was used for all thermodynamic calculations.